2018
DOI: 10.1103/physreve.97.062904
|View full text |Cite
|
Sign up to set email alerts
|

Flow of anisometric particles in a quasi-two-dimensional hopper

Abstract: The stationary flow field in a quasi-two-dimensional hopper is investigated experimentally. The behavior of materials consisting of beads and elongated particles with different aspect ratio is compared. We show, that while the vertical velocity in the flowing region can be fitted with a Gaussian function for beads, in the case of elongated grains the flowing channel is narrower and is bordered with sharper velocity gradient. For this case, we quantify deviations from the Gaussian velocity profile. Relative vel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
(65 reference statements)
5
16
0
Order By: Relevance
“…The velocity distribution curve gradually flattens along the upward direction and eventually forms a plateau in the horizontal central zone, that is, a plug flow zone is formed in the upper part of the flowing zone. Such phenomenon has also been experimentally observed for funnel flow discharge 21–25 . Szabo et al 25 found the formation of plug flow zone was closely related to the particle shape.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The velocity distribution curve gradually flattens along the upward direction and eventually forms a plateau in the horizontal central zone, that is, a plug flow zone is formed in the upper part of the flowing zone. Such phenomenon has also been experimentally observed for funnel flow discharge 21–25 . Szabo et al 25 found the formation of plug flow zone was closely related to the particle shape.…”
Section: Resultssupporting
confidence: 58%
“…Such phenomenon has also been experimentally observed for funnel flow discharge 21–25 . Szabo et al 25 found the formation of plug flow zone was closely related to the particle shape. Their experimental results showed that the position of plug flow zone was closer to the outlet for longer grains.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Most experiments and numerical simulations have been performed with hard monodisperse spherical grains in the past. Few experiments of non-spherical shapes 19,[26][27][28] demonstrated that many features of the discharge can be compared to those of spheres when an effective particle radius is introduced. Examples of numerical simulations of silo discharge of nonspherical particles with multisphere-DEM include rods 29 and mixtures of spherical and rodlike grains.…”
Section: Introductionmentioning
confidence: 99%
“…In all discharge experiments, we placed the capsules initially in random orientations. However, elongated grains typically display alignment near the outlet of a discharging hopper [21,22], an aspect that may be influenced by activity of the grains. In Fig.…”
Section: Passage Through Orificesmentioning
confidence: 99%